Physical activity is a potential measure of physical resilience in older adults receiving hemodialysis - Lucas, Anika; Rutledge, Jeanette; Sloane, Richard; Hall, Katherine; Green, Ciara; Pieper, Carl; Colón-Emeric, Cathleen; Hall, Rasheeda (Frontiers in Nephrology, 2023)
Background: Physical resilience, or the ability to recover after a physical stressor, declines with aging. Efforts to preserve physical resilience in the older dialysis population are critically needed; however, validated, patient-centered measures that are sensitive to change are also needed. Our objective was to assess accelerometer-derived step count variability, or a measure of intra-individual variation in physical activity, as a potential measure of physical resilience among older adults receiving hemodialysis. Methods: Community-dwelling ambulatory older adults receiving in-center hemodialysis were prospectively enrolled. Participants wore wrist accelerometers during daytime hours on both dialysis and non-dialysis days up to 14 days, and the feasibility of accelerometer use was assessed from wear time. We used accelerometer data to compute step counts in 4-hour blocks and step count variability. Physical function was assessed with the Short Physical Performance Battery (SPPB which includes gait speed test), grip strength, activities of daily living (ADLs) instruments, and life space mobility. We assessed interval fatigue (subjective rating from 0 to 10) on dialysis and non-dialysis days and self-reported recovery time. We assessed the correlations of step count variability with measures of physical function and step count and interval fatigue. Results: Of 37 enrolled participants, 29 had sufficient accelerometer data for analyses. Among the 29 participants, mean (SD) age was 70.6(4.8) years, and 55% (n=16) were male and 72% (n=21) were Black race. Participants were largely sedentary with median (Q1-Q3) self-reported total kilocalories per week of 200 (36-552). Step count variability was positively correlated with measures of physical function: SPPB (r=0.50, p<0.05), gait speed (r=0.59, p<0.05), handgrip strength (r=0.71, p<0.05), Instrumental ADLs (r=0.44, p<0.05) and life space mobility (r=0.54, p<0.05).There was a weak inverse correlation between post-dialysis step counts (4-hour blocks after a dialysis session) and post-dialysis interval fatigue [r=-0.19 (n=102, p=0.06). Conclusions: Physical activity assessment via accelerometer is feasible for older adults receiving hemodialysis. Step count variability correlated with physical function, so it may be a novel measure of physical resilience. Further studies are needed to validate this measure.